El problema del mal desde la Filosofía de la realidad histórica de Ignacio Ellacuría - Brito de Butter, Marcela Lisseth (2022)
This paper aims to provide an analytical proposal on the problem of evil from the category of historical reality, of the philosopher Ignacio Ellacuría, in response to the inadequacies present in other contemporary approaches.